Fault diagnosis method for rotor system of centrifugal compressor units - LIU Baoxia; WANG Meng; MA Yulei (You-qi chuyun, 2023)
The rotor system of the centrifugal compressor unit comprises the rotor and the support structure. The change in the rotor balance state and the abnormal stiffness of the composite spring are common faults of the rotor system. However, the simultaneous occurrence of the above two will result in an abnormal vibration that is not easy to be distinguished. In order to identify and diagnose such faults accurately, a rotor vibration analysis model was established to analyze the change in the rotor unbalance state and the abnormal stiffness of composite spring at different rotating speeds. Meanwhile, the influence of such faults on vibration was studied. The results show that the rotor vibration response will produce a series of regular changes when the above two faults occur. The relevant theories were verified by practical application, providing theoretical and practical support for the identification and analysis of the fault. Generally,the research results could assist the field staff to find the abnormal state of rotor balance, the abnormal stiffness of the composite spring,and the complex fault at the simultaneous occurrence of the two. This is helpful to judge the fault location, find out the fault cause and formulate the targeted maintenance plan, so as to ensure the safe operation of centrifugal compressor units in long-distance natural gas pipelines.